Risk and protective factors for inpatient aggression - Vries Robbé, Michiel de (Criminal justice and behavior, 2016)
Dynamic risk and protective factors serve to assess the violence risk level of (forensic) psychiatric patients and offer guidance to clinical interventions. Risk assessment scores on Historical Clinical Risk Management?20 (HCR-20) risk factors and Structured Assessment of Protective Factors for violence risk (SAPROF) protective factors at different treatment stages were compared with violent incidents during treatment for 399 multidisciplinary coded assessments on 185 male and female forensic psychiatric patients. At later stages of treatment, less risk factors and more protective factors were observed, and predictive validities were higher. The HCR-20 and SAPROF scores showed good overall predictive validity for inpatient violence. The combination of risk factors and protective factors was a good predictor of incidents of aggressive behavior for different groups of patients, such as patients with violent or sexual offending histories, patients with major mental illnesses or personality disorders, and patients with a high score on psychopathy. Implications of these findings and recommendations for future research are discussed.